Factors influencing participation of underrepresented students in STEM fields: matched mentors and mindsets - Katherine Kricorian; Michelle Seu; Daniel Lopez; Elsie Ureta; Ozlem Equils (SpringerOpen, 2020)
Abstract Background Women and ethnic minorities remain underrepresented in science, technology, engineering, and math (STEM) fields. The goal of this pilot study is to better understand the beliefs and experiences of underrepresented US students pursuing STEM. Our focus was to gain insights into their mentorship experiences and preferences regarding having mentors who are gender and ethnicity matched. Environmental and psychological factors associated with participants' decision to pursue STEM, such as family influences, academic mindsets, and attitudes towards STEM, were also studied. Methods We developed a survey tool based on published literature and established instruments, including measures of STEM belonging, science identity, and growth mindset, as well as measures assessing students' views on their STEM participation. We surveyed members of a STEM-focused non-profit who were in college, graduate school, or were recent graduates. Results Forty-eight adults currently pursuing STEM responded to the survey. The majority (71%) were female and nearly all (96%) identified as an ethnic minority. Most reported knowing someone of their same gender (68%) or ethnicity (66%) with a STEM career who served as a role model. The majority (54%) stated that meeting a STEM professional of their own gender and ethnicity would be effective encouragement to pursue STEM. A similar percentage (56%) believed that media exposure to gender- and ethnicity-matched STEM professionals would be effective encouragement. Most (73%) demonstrated a growth mindset and had strong family support to pursue STEM (68%). Only two-thirds (66%) felt they belonged in STEM careers, and 30% agreed that people in their STEM classes are a lot like them. Conclusion This study contributes additional information on the views and experiences of diverse students actively pursuing STEM. Most participants indicated the importance of meeting and being mentored in STEM by those of their same gender and ethnicity, either in person or through media. Future educational efforts to increase STEM diversity should consider students' mentorship preferences and facilitate interactions with matched-background mentors accordingly, with consideration given to the use of media. Educators should focus on inclusive learning by highlighting the accomplishments of diverse STEM professionals, to help strengthen feelings of STEM belonging.